Geolocating for Web Based Geospatial Applications - Veenendaal, Bert; Delfos, Jacob; Tan, Tele (CRC Press, Taylor and Francis Group, 2011)
The geospatial location of stationary and mobile objects and phenomena are increasingly important to geospatial applications. The availability and ease of access to geospatial information and digital earth technologies via the Internet are helping to drive a greater demand for geolocating fixed and mobile features, users, assets, services and other phenomena. A range of methods are used to determine spatial locations of fixed and mobile objects and properties including GPS, WiFi, RFID, geocoding, sensors and IP locating. Current research is investigating methods to identify user locations on the internet. The internet forms an attractive platform for Location Based Services (LBS) since it provides a nearly ubiquitous medium and web browsers provide a highly standardised application environment. However, security mechanisms in browsers complicate communication with devices used for positioning. IP positioning can provide a viable alternative, particularly since the computer network hierarchy is related to spatial hierarchies. This chapter introduces location based services and the importance of location. A range of methods for obtaining geospatial location are introduced and the contexts in which they are used are described. Finally, some current research is outlined where a methodology known as VRILS was developed to enable the use of IP addresses for geolocating in a web based environment.